Enhanced Fasanella–Servat Procedure for the Graded Repair of Blepharoptosis. Issue 6 (November 2017) - North, Victoria S.; Campbell, Ashley A.; Callahan, Alison B.; Wilcsek, Geoff; Kazim, Michael
Abstract : Purpose: To describe in detail a technique for a modified Fasanella–Servat procedure that provides a simplified method for graded Mueller muscle excision with minimal and controlled tarsal excision. Methods: A retrospective study of 71 patients (102 eyelids) who underwent the modified Fasanella–Servat procedure is reported. Measurements include the preoperative, post-phenylephrine, and postoperative margin-to-reflex distance-1, and postoperative upper eyelid height symmetry as determined by the absolute difference between right- and left-sided margin-to-reflex distance-1. Postoperative complications are reported. Results: The average increase in margin-to-reflex distance-1 was 2.4 mm with an average postoperative upper eyelid height symmetry of 0.4 mm. Postoperative asymmetry was 1.5 mm or less in 68 patients, a success rate of 96%. Four patients (6%) exhibited overcorrection, 2 of which required additional surgery. No lagophthalmos or notable eyelid contour abnormalities were seen. Conclusions: The modified Fasanella–Servat technique offers a simple method to isolate and resect Mueller muscle and a minimal segment of tarsus in a quantitative fashion, allowing for a graded repair of blepharoptosis and thereby decreasing the risk of postoperative overcorrection, lagophthalmos, and eyelid contour asymmetry whilst preserving the bulk of tarsus. Abstract : The Fasanella–Servat procedure for the correction of selected cases of ptosis has been modified with excellent outcomes to increase predictability by allowing independent and graded Mueller muscle resection and controlled excision of tarsus.